Slotted floors for swine - Koch, B.A. (Kansas Agricultural Experiment Station, 2011)
Slotted floors in all phases of swine production are being widely investigated. Confining pigs on a slotted floor is not a new idea. However, we need to know more about how best to use slotted floors.
Keywords: Swine; Slotted floors; Performance